High Thermoelectric Performance in Earth‐Abundant Cu3SbS4 by Promoting Doping Efficiency via Rational Vacancy Design. (17th January 2023) - Zhang, De; Wang, Xincan; Wu, Hong; Huang, Yuling; Zheng, Sikang; Zhang, Bin; Fu, Huixia; Cheng, Zien; Jiang, Pengfei; Han, Guang; Wang, Guoyu; Zhou, Xiaoyuan; et al.
Abstract: Sulfides are well investigated as thermoelectric materials but their performance is typically limited by low electrical conductivity. High electrical performance in Cu3 SbS4 is reported by creating high valence vacancies, which efficiently provides multiple carriers. It is revealed from the perspective of a chemical bond by calculations that Al can serve as vacancy stabilizer as its entry into the lattice forms intensified bonds with neighboring atoms and lowers the vacancy formation energy. As a result, the average power factor of Cu3 SbS4 with 9 wt% CuAlS2 reaches 16.1 µW cm −1 K −2 . Finally, by further addition of AgAlS2, a peak zT of 1.3 and an average zT of 0.77 are obtained due to the reduced thermal conductivity. The attained average power factor and average zT are superior to other low‐toxic thermoelectric sulfides. The findings shed light on the new strategy for creating favorable vacancies to realize high‐efficiency doping in thermoelectric materials. Abstract : The high valence vacancy Sb can be stabilized by Al atom, which causes intensified chemical bonds and lowers the formation energy of Sb vacancy. These high valance vacancies can efficiently provide multiple carriers in Cu3 SbS4 and realize high doping efficiency. As a result, both superior thermoelectric performance and high power factor are attained in Cu3 SbS4, which is among the best in low‐toxic thermoelectric sulfides.